Molybdenum-based nanoclusters act as antioxidants and ameliorate acute kidney injury in mice. Issue 1 (December 2018) - Ni, Dalong; Jiang, Dawei; Kutyreff, Christopher; Lai, Jianhao; Yan, Yongjun; Barnhart, Todd; Yu, Bo; Im, Hyung-Jun; Kang, Lei; Cho, Steve; Liu, Zhaofei; Huang, Peng; et al.
Abstract Acute kidney injury (AKI) is a common reactive oxygen species (ROS)-related renal disease that causes numerous deaths annually, yet only supportive treatment is currently available in the clinics. Development of antioxidants with high accumulation rates in kidneys is highly desired to help prevent AKI. Here we report molybdenum-based polyoxometalate (POM) nanoclusters with preferential renal uptake as novel nano-antioxidants for kidney protection. These POM nanoclusters, with a readily variable valence state of molybdenum ions, possess the capability to scavenge detrimental ROS. Our results demonstrate that POM nanoclusters can efficiently alleviate clinical symptoms in mice subjected to AKI, as verified by dynamic PET imaging with68 Ga-EDTA, serum tests, kidney tissue staining, and biomarkers detection in the kidneys. The protective effect of POM nanoclusters against AKI in living animals suggests exploring their use for the treatment of AKI patients, as well as patients with other ROS-related diseases. There are currently no effective therapies available for acute kidney injury (AKI). Here the authors generate molybdenum-based polyoxometalate nanoclusters and show that these have preferential renal uptake and can ameliorate AKI pathology in mice by scavenging reactive oxygen species.